PERAN FORUM KERUKUNAN UMAT BERAGAMA DALAM MENGEMBANGKAN NILAI TOLERANSI DI KABUPATEN BEKASI - Sirait, Mutiara Octavia Br (Civic Education Program, Universitas Negeri Semarang, 2017)
Abstract: This research to examined the role of Forum Kerukunan Umat Beragama (FKUB, the strategies of used, as well as the supporting and obstacles’s factor faced by FKUB in developing the value of tolerance in Bekasi Regency. The location of this research was in FKUB office, Sinyar Barat street No 10, Karangsari Village, Cikarang Timur District, Bekasi Regency. This research used a qualitative’s method with data collecting by interviewing, observation and documentation. The result showed that the role of FKUB in developing the value of tolerance in Bekasi Regency including three important roles,they are : the are role as figure religious includes helping the government to resolve the conflicts, the role model for his followers, teaching the religious pluralism As the member of FKUB including: the implementers of the socialization program PBM, helping the government to resolve conflict between the religious communities, active in dialogue with society,reviewing the recommendations a permit for the establishment of worship’s house. As the officials including implementers, the communicator and coordinator of the FKUB’s program. The strategy and media that used dialogue, although there isn’t the special media, only by socializing through the districts/wards. FKUB programs in developing value of tolerance is the socialization PBM No. 9/8 2006, dialogue with community organizations and figures. The supporting and obstacles’s factor in developing tolerance of value in Bekasi regency consists of internal and external. Suggestion in this research are: for FKUB as the government’s partners keep trying to socialize PBM so that people be able understand. For local governments, providing the official office and establishing a permanent budget for FKUB on implementing it’s program. For the society, supporting FKUB in efforts in developing value of tolerance and keeping the religious harmony in Bekasi regency.